Using netnography research method to reveal the underlying dimensions of the customer/tourist experience - Rageh, Ahmed; Melewar, T.C.; Woodside, Arch (Emerald Group Publishing Limited, 2013)
Purpose – The interest in customer experience has increased at a phenomenal rate.However, research to capture the true meaning of the concept is limited.Therefore, this study aims to address the question of what are the underlying dimensions that constitute the construct of customer experience.Design/methodology/approach – The netnography method is utilized to validate a priori concepts that have been identified in the literature within the tourist industry in Egypt. Findings – The results identified eight dimensions; comfort, educational, hedonic, novelty, recognition, relational, safety and beauty, which are consistent with major studies on experience.Research limitations/implications – The focus of the study was on customer reviews that were written in English and posted online. Therefore, care should be taken when interpreting these findings.Practical implications – This study attempted to gain a meaningful degree of understanding of customer experience construct. The results suggest a number of implications for service, marketing and brand managers.The knowledge of customer experience and the challenge of creating great customer experience are of utmost importance.Many marketers acknowledge the importance of customer experience, but they have very little knowledge of what the components are of customer experience.Originality/value – Netnography has not been widely used as a marketing research technique.